Education Marketing Management Strategy in Improving School Quality in MTs Darul Hikmah, Tangjungkerta District, Sumedang Regency - Paroli Paroli (SINTESA, 2023)
Marketing management in an educational institution is very important. This is the desire of education consumers to know what is in the school. In that case, an education management strategy is needed to carry out good and correct marketing according to existing conditions. When marketing a school, what must be considered is the quality of the school as something that will be offered to the market. The implementation of an education marketing management strategy will be good if it is supported by good school quality. However, there are still schools that have not integrated the two well. This research aims to determine the education management strategy carried out at MTs Darul Hikmah, Tangjungkerta District, Sumedang Regency and to determine the quality of school at MTs Darul Hikmah. The research method used is qualitative research. The results of this research indicate that MTs Darul Hikmah, Tangjungkerta District, Sumedang Regency has implemented an education marketing management strategy and the quality of the school is quite good, although improvements are still needed for the future